Distribution characteristics of ABO blood groups in China. Issue 9 (September 2022) - Sun, Yang; Wang, Liqin; Niu, Jiameng; Ma, Ting; Xing, Lili; Song, Aowei; Wang, Wenhua; Shen, Yuan; Yang, Jiangcun
Abstract: ABO blood groups distribution shows obvious geographical differences globally, but the reliability of the Blood data for assessing relationships between population groups is limited. This is mostly due to the lack of availability and interchange of this important data. We collected data of 23 million ABO blood group population from 34 provincial-level administrative regions in China. To ensure the reliability of the results, we standardized the 23 million data by the China seventh census data. The ranking of ABO blood groups phenotypic distribution in China is O > A > B > AB. The proportions of A, B, O and AB type in China population are 28.72%, 28.17%, 34.20%, and 8.91%, respectively. Accordingly, the frequencies of p [A], q [B], and r [O] gene at the ABO blood group are 0.211, 0.208, and 0.584, respectively. China blood phenotype is dominated by O type, but the r gene frequency is obviously lower than other countries. The distribution of ABO blood groups in China varies geographically. Clustering analysis results show that ABO blood groups divide into four regions from north to south in China, and reveal that the r [O] gene shows an increasing trend from North to South, and conversely the q [B] gene exhibited a decreasing trend at these coordinates. These analyses present interesting characteristics of the blood group distribution across the geography of China. Abstract : China population; ABO blood group; Phenotype; Gene frequency, Distribution characteristics.